A Diuretic Protocol Increases Volume Removal and Reduces Readmissions Among Hospitalized Patients With Acute Decompensated Heart Failure. Issue 2 (21st January 2013) - Barsuk, Jeffrey H.; Gordon, Robert A.; Cohen, Elaine R.; Cotts, William G.; Malkenson, David; Yancy, Clyde W.; Williams, Mark V.
<x xml:space="preserve">Abstract</x> Despite the widespread use of loop diuretics to treat acute decompensated heart failure (ADHF), robust data supporting their role and optimal dosing strategies are scarce. This analysis aimed to compare clinical outcomes of patients admitted with ADHF who received a diuretic dosing protocol with those who received the usual diuretic therapy. We performed an observational medical records review to compare the use of a nurse‐driven diuretic dosing protocol with usual diuretic dosing for patients admitted with ADHF during a 1‐year period. Using a propensity scoring model, comparisons were made between groups for total weight loss, length of stay (LOS), 30‐day readmissions, in‐hospital mortality, 30‐day mortality, and acute kidney failure. Sixty‐eight of the 596 patients admitted with ADHF during the study period received the diuretic protocol. Protocol use was associated with an additional 2.63‐kg weight loss (P=.003) but a trend toward increased LOS compared with patients receiving usual care (P=.097). However, patients receiving the protocol had a significantly lower risk of 30‐day readmission (odds ratio, 0.46, 95% confidence interval, 0.22–0.95). Protocol use was not associated with significant differences in kidney failure, inpatient mortality, or 30‐day mortality. A diuretic dosing protocol for patients admitted with ADHF improves weight loss and may lower 30‐day readmissions, at the cost of potentially increasing LOS.